Provision with time and its use as essential households resource - I. A. Kulkova; N. P. Neklyudova (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study the time as the most important resource of each household. The topic relevance is determined by the importance of time as households’ economic resource and its insufficient knowledge. The aim of the study is to assess the degree of households’ resourcing with a time and to develop a spending free time typology. The concepts of leisure and leisure activities are reflected in the work. Authors’ calculations are made that allow to determine the households’ provision with a time resource. The scientific novelty of the study is the proposed leisure activities classification by various logical basis. Household members who experience problems in terms of leisure activities are in this paper also